Toward sustainable indoor environments: assessing the impact of thermal insulation measures on air quality in buildings ; a case study in Temuco, Chile - Martínez-Soto, Aner; Jimenez-Gallardo, Carlos; Villarroel-Lopez, Andrés; Reyes-Riveros, Alejandro; Höhl, Johanna (Sustainability, 2024)
In Chile, an Atmospheric Decontamination Plan (PDA) has been developed to reduce concentrations of fine particulate matter (PM 2.5) in cities deemed “saturated” with these particles. The plan includes various measures, such as the thermal insulation of homes and the replacement of heaters. This study presents an analysis of the indices of four indoor air quality variables (temperature, humidity, carbon dioxide, and PM 2.5) in different types of homes with varying levels of PDA implementation in the city of Temuco, Chile. Regarding the temperature variable, only one type of home was found to be within comfort limits, with an average of 20.6 °C and a variation of ±3.52 °C (SD). Concerning humidity, independently owned homes with complete and moderate ADP implementation had average humidity levels between 64.82% ± 7.19% and 55.6% ± 6.11%, respectively. For CO2, only homes with moderate implementation showed averages slightly below (average 991 ppm) the maximum allowed (1000 ppm). As for PM 2.5, all homes exceeded the standard, ranging from 44.4 µg/m3 to 130 µg/m3, with very high variations. This demonstrates that PM 2.5 concentrations consistently exceeded the limits established by the World Health Organization (15 µg/m3).
Gesehen am 22.08.2024